Intense broadband radioluminescence from an Mn2+-doped aluminoborate glass scintillator. Issue 28 (6th July 2022) - Chen, SunYueZi; Gong, YuJia; Huang, WenJun; Wen, ZhuoXing; Li, LianJie; Ashraf, Ghulam Abbas; Lei, Lei; Cao, JiangKun; Guo, Hai
Abstract : A novel broad-band emission glass scintillator is designed under redox control with greatly enhanced PL (7.2 times) and XEL (1.8 times) performances. Abstract : Alternative scintillating materials are of current interest for radiation detection in diverse high-energy applications, e.g., in X-ray imaging and high-energy physics. However, single crystals as the main material for scintillators hinder the preparation with large size, low cost, and diverse shape. Here, we offer an easy preparation procedure of Mn 2+ -activated aluminoborate glasses under air atmosphere by the traditional melt-quenching approach. These glass specimens exhibit broadband photoluminescence and radioluminescence under ultra-violet light and X-ray excitation, respectively. Moreover, the reduction of Mn 3+ to Mn 2+ leads to improved scintillating performance, favoring the preparation of Mn 2+ -doped scintillating glasses under air atmosphere. The energy transfer from Gd 3+ to Mn 2+ contributes to both photoluminescence and radioluminescence and the energy transfer efficiency reaches 96.4%. More notably, the integrated X-ray excited luminescence intensity from the optimal specimen is 42.2% that of the commercial Bi4 Ge3 O12 single crystal scintillator, offering great potential in X-ray detection and large area imaging.